Nutritional status of under-five pulmonary tuberculosis patients before and after six-month therapy - Barita Sidabutar; Soepardi Soedibyo; Alan Tumbelaka (Paediatrica Indonesiana, 2004)
Background Tuberculosis (TB) is a chronic infectious diseasewhich remains a health problem throughout the world including inIndonesia. The implementation of directly observed treatment short-course (DOTS) strategy will hopefully increase patient’s compli-ance, so that a minimum of 85% cure rate could be achieved. Thesuccess in coping with TB disease is expected to become one offactors that play role in providing a solution for malnutrition prob-lems in Indonesia, especially for those caused by TB.Objective The aim of this study was to determine the distributionof nutritional status of under-five TB patients before and after six -month therapy.Methods We reviewed under-five children with pulmonary TB vis-iting the Pediatric Pulmonology Outpatients Clinic of CiptoMangunkusumo Hospital from January 1999 to December 2001.Results Using the weight-for-age (W/A) indices, from 279 patients,the proportion of well-, under-, and severe-malnourished statuswas 36.9%, 60.2%, and 2.9%, respectively, and after 6-monththerapy it became 58.8%, 39.8%, and 1.4%, respectively.Conclusion After 6 months of therapy, the nutritional status of TBpatients increased